ANALISIS PERBANDINGAN STABILITAS LERENG PADA AREA KARST (STUDI KASUS GIRIMULYO, KULON PROGO) - Anisa Nur Amalina; Azmi Aufa Ifthikar (UKI Press, 2025)
Girimulyo District, Kulon Progo, is famous for its karst landscape, making it one of the tourist destinations. This location is mainly composed of easily soluble rocks such as limestone, dolomite, gypsum, and rock salt, making it very susceptible to landslides, thus requiring a comprehensive slope stability analysis to reduce the risk of landslides that impact residential areas, access roads, and tourist locations. This study evaluated slope stability using the Limit Equilibrium Method (LEM) and the Finite Element Method (FEM). The slope at the research location consists of a layer of silt on the surface and limestone at a depth of 9 meters. Slope modeling was carried out in static and pseudo-static conditions by combining horizontal seismic coefficients derived from SNI 1726 (2019). The results showed that most LEM methods, except the Fellenius method, had higher SF than the FEM method. All methods showed that the slope in the static condition is stable with a safety factor (SF) ≥ 1.25, while in the pseudo-static condition, all methods are considered unstable (SF ≤ 1.07). Among the LEM approaches, the Fellenius (1936) method showed the lowest SF, which is in accordance with previous studies, where this method is the most conservative and suitable for circular slip surfaces only. Meanwhile, the Bishop (1955) and Morgenstern-Price (1965) methods are the most recommended in this study because they accommodate circular and non-circular slip surfaces. The SF results are 2% higher than the FEM results. These results show the importance of choosing the proper analysis method for landslide-prone karst terrain such as Girimulyo. Keywords: FEM; LEM; PLAXIS 2D; slope/W; SF